Uso de evidências pela burocracia dirigente do nível federal - Pedro Lucas de Moura Palotti; Natália Massaco Koga; Bruno Gontyjo Do Couto; Maricilene Isaira Baia Do Nascimento; Rafael da Silva Lins (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This research aims to draw a radiograph of the use of evidence by senior bureaucrats of the federal government, from a survey applied between November 2020 and January 2021, with 787 occupants of management and advisory positions (DAS), levels 4, 5 and 6 and related, in organizations of the Direct and Indirect Administration. As part of the project "What informs public policies: the use and non-use of evidence by the federal bureaucracy", the study explores questions about the constraints and purposes of the use of scientific evidence by senior bureaucrats, in comparison with the results of a survey conducted in 2019 with the general universe of federal bureaucrats. The present study innovates by proposing experiments in survey and brings as main results: i) the preponderance of internal sources among the informational resources used by senior bureaucrats - a pattern already identified in the 2019 survey; ii) the high potential of absorption of scientific evidence by senior bureaucrats, given the high analytical capacity they accumulated and the relational nature of the tasks they perform; and iii) the identification of challenges related to the development of organizational capabilities and governance systems for the expansion of use of scientific evidence in the federal government.
Keywords: D73; 330; evidence-based policies; evidence; senior bureaucrats; bureaucracy; analytical capacity; governance of evidence